Dairy as a Source of Iodine and Protein in the UK: Implications for Human Health Across the Life Course, and Future Policy and Research - Witard, Oliver C.; Bath, Sarah C.; Dineva, Mariana; Sellem, Laury; Mulet-Cabero, Ana-Isabel; Dongen, Laura H. van; Zheng, Ju-Sheng; Valenzuela, Carina; Smeuninx, Benoit (Frontiers in Nutrition, 2022)
This narrative review summarises key concepts in dairy nutrition for supporting human health throughout the life course. Milk and dairy products have been a staple component of our diet for thousands of years and provide a wide range of important nutrients that are otherwise difficult to obtain from dairy-free diets. In this review, we provide a broad perspective on the nutritional roles of iodine and dairy protein in supporting human health during pregnancy and early life, childhood and adolescence, mid- and later-life. New methodologies to identify biomarkers of dairy intake via high-throughput mass spectrometry are discussed, and new concepts such as the role of the food matrix in dairy nutrition are introduced. Finally, future policy and research related to the consumption of dairy and non dairy alternatives for health are discussed with a view to improving nutritional status across the lifespan.